Rhabdomyosarcoma in Ovary- Pathologist's Diagnostic Dilemma. (28th October 2021) - Srivastava, A C; Hussain, F; Patel, T
Abstract: Introduction/Objective: Rhabdomyosarcoma is the most common pediatric soft tissue sarcoma. However, rhabdomyosarcoma in the ovary is exceptionally unusual and presents a diagnostic challenge. We report one such case and its clinical and pathological perspective. Methods/Case Report: 16-year-old female presented with an enlarging pelvic mass, abdominal distension, and pain. Imaging revealed a heterogeneous left ovarian mass, right axillary lymphadenopathy, and right-hand soft tissue mass. CA-125 was 1833.0 U/ml. Patient underwent left salphingo-oophorectomy, omentectomy, peritoneal and mesenteric biopsy for ovarian staging, incidental appendectomy, and right axillary lymph node excision with suspicion of ovarian epithelial tumor. Pathological evaluation revealed a 16-cm intact ovary with multiple solid and cystic nodules with areas of hemorrhage and necrosis. Microscopic examination of ovarian tumor showed a high-grade malignant tumor consisting of sheets of small round blue cells with severe cytologic atypia, increased mitoses, and features suggestive of rhabdoid morphology. The other specimens were positive for metastases. The tumor cells were immunopositive for Myogenin and MyoD1 while immunonegative for Cytokeratin AE1/AE3, SF-1, PLAP, SALL4, MelanA, and S-100. INI-1 and BRG-1 demonstrated intact nuclear expression. FISH testing identified rearrangement of the FOX01 gene at 13q14. Based on these findings, diagnosis of alveolar rhabdomyosarcoma was rendered. Currently, the patient is receiving rhabdomyosarcoma chemotherapy treatment and has responded well. Results (if a Case Study enter NA): NA Conclusion: In cases with complex and urgent clinical presentation, where the existence of a primary tumor is unknown and where symptoms attributable to primary ovarian tumor dominate the clinical picture, rhabdomyosarcoma is rarely proposed in the differential diagnoses of small round blue cell tumors of the ovary. At present, the right-hand mass is under evaluation; thus, the true nature of the ovarian mass, primary or metastatic is unknown. Our case illustrates the importance of exact diagnoses, as treatment of rhabdomyosarcoma, is different from other ovarian tumors.